THE EFFECTS OF BACKGROUND MUSIC DIMENSIONS ON CUSTOMER ATTITUDE TOWARDS RETAIL STORE - Ovali, Esra (FUTURE ACAD, 2019)
As a key ambient factor in retail environment, music can refresh and create pleasurable memories and experiences for the shoppers. However, bringing up standardized findings in each study is not applicable. It is important to identify which musical characteristics positively affect the customers, allowing them to spend more time and money for shopping in retail stores. The content of those factors and the findings of past studies are emphasized due to national and international literatures. The purpose of this research is to identify the effects of background music dimensions (tempo and loudness) on customer attitude towards small-scale sporting goods retail stores. In accordance with this aim, subsequent to an in depth literature review, a conceptual framework was comprised and tested by means of statistical analysis of primary data collected by a questionnaire from 247 customers, shopping from a sporting goods store at Istanbul city center. Two conditions related tempo (fast / slow) and loudness (loud / soft) were organized as independent variables. A questionnaire respecting attitude towards store was applied to be responded by customers exposed to background music in the store. Experimental groups of 'fast tempo and high loudness' and 'slow tempo and low loudness' do not have a statistically significant effect on attitude towards the store. Hereby, correlation analysis is the major statistical method in the research. The findings define that the effects of tempo and loudness on customer attitude towards small-scale sporting goods store on a busy street are differentiated according to tempo and loudness groups. (C) 2019 Published by Future Academy www.FutureAcademy.org.uk
Keywords: Background music; attitude; tempo; loudness; retail; IMPACT; ATMOSPHERICS; ENVIRONMENT; PERCEPTION; CONGRUITY; BEHAVIOR; Business & Economics